Effect of Calcium-enriched Mixture (CEM) cement on increasing mineralization in stem cells from the dental pulps of human exfoliated deciduous teeth - Rezvan Rafatjou; Iraj Amiri; Atousa Janeshin (Tabriz University of Medical Sciences, 2018)
Background.Stem cells isolated from human exfoliated deciduous teeth (SHED) are highly capable of proliferation and differentiation into odontogenic, osteogenic, adipose tissue and neural cells. The aim of this study was to investigate the effect of CEM cement on increasing mineralization in stem cells of exfoliated deciduous teeth. Methods.Dental pulps were isolated from extracted exfoliating primary teeth and immersed in a digestive solution. The dental pulp cells were immersed in α-MEM (modified culture medium) and 10% fetal bovine serum (FBS) was added. The culture cells were used for mineral deposit formation after the third passage. The cells were cultured in osteogenic cell culture medium in the control group and in osteogenic culture medium supplemented with CEM cement in the case group. Alizarin red staining was used to evaluate the mineral deposit formation on day 21. Statistical significance was determined with t-test. Results.Quantification of alizarin red staining showed that cells exposed to CEM cement induced more mineralized nodules (P=0.03). Conclusion.Mineral deposit formation in SHEDs was stimulated by CEM cement. Based on these data it might be suggested that CEM could improve osteoblastic differentiation.